Short-range airborne route dominates exposure of respiratory infection during close contact - Chen, Wenzhao; Zhang, Nan; Wei, Jianjian; Yen, Hui-Ling; Li, Yuguo (Building and environment, 2020)
A susceptible person experiences the highest exposure risk of respiratory infection when he or she is in close proximity with an infected person. The large droplet route has been commonly believed to be dominant for most respiratory infections since the early 20th century, and the associated droplet precaution is widely known and practiced in hospitals and in the community. The mechanism of exposure to droplets expired at close contact, however, remains surprisingly unexplored. In this study, the exposure to exhaled droplets during close contact (<2 m) via both the short-range airborne and large droplet sub-routes is studied using a simple mathematical model of expired flows and droplet dispersion/deposition/inhalation, which enables the calculation of exposure due to both deposition and inhalation. The short-range airborne route is found to dominate at most distances studied during both talking and coughing. The large droplet route only dominates when the droplets are larger than 100 μm and when the subjects are within 0.2 m while talking or 0.5 m while coughing. The smaller the exhaled droplets, the more important the short-range airborne route. The large droplet route contributes less than 10% of exposure when the droplets are smaller than 50 μm and when the subjects are more than 0.3 m apart, even while coughing. •The smaller the exhaled droplets, the more important the short-range airborne route.•Exhalation velocity impacts significantly on droplet travel distance and size change.•The large droplet route only dominates when the subjects are within 0.2 m while talking or 0.5 m while coughing.•The large droplet route contributes less than 10% of exposure when the droplets are smaller than 50 μm at 0.3 m apart.